Unusual Foreign Bodies in the Lower Genitourinary Tract (Journal of Enam Medical College, 2018)
Foreign body in the lower genitourinary tract is a relatively rare occurrence. A variety of foreign bodies have been reported in the literature. Commonly reported condition under which foreign bodies are introduced into genitourinary tract is autoeroticism. The highest incidence occurs in homosexuals, lesbians and masochism. But self-introduction of foreign body in the vagina in a 5-year-old girl is an extremely rare occurrence. Here we report two cases of self-inserted lower genitourinary foreign body in two different ages.J Enam Med Col 2018; 8(2): 105-107